Weakening Dust Storm Intensity in Arid Central Asia Due to Global Warming Over the Past 160 Years - Zhang, Jin; Xu, Hai; Lan, Jianghu; Ai, Li; Sheng, Enguo; Yan, Dongna; Zhou, Kang’en; Yu, Keke; Song, Yunping; Zhang, Shuang; Torfstein, Adi (Frontiers in Earth Science, 2020)
Dust storms occur frequently in arid central Asia (ACA) and greatly influence the regional ecology/environment, human health and security, as well as the global climate. To date, neither the patterns nor the underlying mechanisms of dust storms in ACA are fully understood, partly due to the lack of long term historical records. Here we reconstruct a dust storm history of the past ~160 years in northwest China, based on high resolution sedimentary proxies retrieved from Lake Karakul (located in the core zone of ACA). We find that changes in the sedimentary coarse fraction (grainsize >64μm) in Lake Karakul are correlated with both historical and modern observed dust storms. The reconstructed dust storm intensity shows a decreasing trend since AD 1850s, with three high occurrence intervals at AD 1870s-1910s, AD 1930s-1940s, and AD 1960s-1980s. We contend that changes in temperature and wind speed could have dominated the frequency and intensity of dust storms in northwest China during the record periods: temperature controls the wind speed and then the dust storm frequency/intensity; lower temperature corresponding to higher wind speed, and higher dust storm frequency/intensity, and vice versa. The observed anthropogenic global warming could have led to decrease in atmospheric temperature gradients and decline in wind speed, and then decreasing dust storm frequency/intensity. Providing this stands, less and weaker dust storms are expected under a continuously anthropogenic warming scenario.